Acquired common variable hypogammaglobulinaemia and lymphoedema. Issue 747 (January 1988) - Lozewicz, S.; Morris, G.; Garbett, N.; Browse, N.; Slavin, B.; Cole, P.
Abstract : Two patients with lymphoedema of the legs developed recurrent respiratory infections and were found to have panhypogammaglobulinaemia. The early recognition and treatment of this form of immunity deficiency in patients with lymphoedema is important in order to prevent recurrent infections which could cause pulmonary damage and further lymphatic stasis.